Safety of simultaneous endoscopic submucosal dissection for two large colorectal neoplasias in the same patient - Min Seob Kwak; Dong-Hoon Yang; Sung Wook Hwang; Jung Ho Bae; Jae Seung Soh; Seohyun Lee; Ho-Su Lee; Hyo Jeong Lee; Sang Hyoung Park; Byong Duk Ye; Jeong-Sik Byeon; Seung-Jae Myung; et al. (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Multiple large colorectal lesions requiring endoscopic submucosal dissection (ESD) are sometimes diagnosed during colonoscopy. We evaluated the feasibility and safety of ESD of two colorectal lesions in one session. Materials and Methods: The lesions of 16 patients who underwent two ESD procedures in a single session (double ESD group) from November 2009 to July 2014 were matched with those of 64 patients who underwent a single ESD procedure (single ESD group) based on the size and location of the lesion and presence of submucosal fibrosis. Results: The net ESD time per patient was longer in double ESD group than in single ESD group (104.0±36.2 vs. 59.1±39.2 min, p<0.001). The net ESD time per lesion tended to be shorter in double ESD group than in single ESD group (49.6±30.0 vs. 59.1±39.2 min, p=0.077). The en bloc resection and curative resection rates did not differ between double ESD and single ESD groups (93.8 % vs. 98.4%, p=0.262; 90.6 % vs. 84.4 %, p=0.534, respectively). The intra- and postprocedural bleeding rates were 12.5% and 0% in double ESD group and 15.6% and 3.1% in single ESD group, respectively. Perforation occurred in two (6.3%) in double ESD group and in six (9.4%) in single ESD group (p=0.715). Conclusion: Compared with the single ESD, two simultaneous colorectal ESD procedures in a patient did not increase complications; the en bloc and curative resection rates were similar when performed a single ESD procedure and two simultaneous ESD procedures. Cite this article as: Kwak MS, Yang DH, Hwang SW, et al. Safety of simultaneous endoscopic submucosal dissection for two large colorectal neoplasias in the same patient. Turk J Gastroenterol 2018; 29: 183-90.